2021
DOI: 10.2147/dmso.s299744
|View full text |Cite
|
Sign up to set email alerts
|

Bone Autophagy: A Potential Way of Exercise-Mediated Meg3/P62/Runx2 Pathway to Regulate Bone Formation in T2DM Mice

Abstract: Background Meg3 has been shown to attenuate T2DM bone autophagy by activating p62 to inhibit bone formation. However, whether exercise can reverse this process to promote T2DM bone formation and its mechanism remains unknown. Methods A T2DM mouse model was established by a high-fat diet and STZ injection, and the mice were trained with 8-week HIIT and downhill running exercise. Micro-CT was used to scan the bone microstructure. Bone morphology was observed by HE stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Our results are in accordance with previous studies showing that HIIT with resistance training can significantly increase the BMD (69, 70). Eight weeks of HIIT and downhill running exercise mediated the Meg3/P62/Runx2 pathway to promote bone formation in T2DM mice (31). However, except for OSX, HIIT did not significantly improve the expression of RUNX2 and ALP compared with the T2DM+NE group.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our results are in accordance with previous studies showing that HIIT with resistance training can significantly increase the BMD (69, 70). Eight weeks of HIIT and downhill running exercise mediated the Meg3/P62/Runx2 pathway to promote bone formation in T2DM mice (31). However, except for OSX, HIIT did not significantly improve the expression of RUNX2 and ALP compared with the T2DM+NE group.…”
Section: Discussionmentioning
confidence: 82%
“…RE was performed three times per week, with three climbs per session and five dynamic movements per climb (26). Group T2DM-HIIT mice underwent 8 weeks of HIIT, the speed of which was 16-26 m/min for 4 min with complete rest for 2 min, in a 10-round cycle, with warm-up and relaxation before and after exercise for 2 min (31). Mice in the T2DM-NE, T2DM-HIIT, T2DM-AE, T2DM-S, and T2DM-RE groups were kept on a HFD during the 8 weeks of exercise (Figure 1).…”
Section: Exercise Protocolmentioning
confidence: 99%
“…41 We then established an in vivo running model using wild-type mice and showed that exercise increases bone mass. 42,43 However, little is known about how macrophages contribute to the mechanical force-induced osteogenesis of BMSCs. It has been determined that a crucial second messenger for macrophage polarization is Ca 2+ inward influx mediated by macrophage-sensitive ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has also demonstrated the advantages of exercise on M2 macrophage polarization and energy homeostasis 41 . We then established an in vivo running model using wild‐type mice and showed that exercise increases bone mass 42,43 . However, little is known about how macrophages contribute to the mechanical force‐induced osteogenesis of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…All animals were adaptively fed for 1 week and then randomly divided into a normal control group (N, n=15) and an obesity model (n=60), respectively fed a normal chow diet 23 and a high-fat diet 24 (formulation in Table S1 ; purchased from Jiangsuxietong Pharmaceutical Bioengineering Co., Ltd. Nanjing, China) for 10 weeks. A body weight ≥20% of the average weight of the normal group was used as the criterion for obesity.…”
Section: Methodsmentioning
confidence: 99%